Analisis Nonparametrik Mann Whitney Terhadap Perbedaan Kemampuan Pemecahan Masalah Menggunakan Model Pembelajaran Problem Based Learning - Andi Quraisy; Setiawan Madya (Universitas Negeri Makassar, 2021)
This study aims to determine whether there are differences in mathematical problem solving abilities in the experimental class and control class using the Problem Based Learning Model. This type of research is a quasi-experimental involving two groups that are given different treatments. The population of this study was class XI SMAS PPM Rahmatul Asri and two classes were selected by cluster random sampling as the research sample, namely class as an experimental class taught using the Problem Based Learning Model, while class as a control class taught using conventional learning. The research instrument used was in the form of a problem-solving ability test in the form of a test in the form of a description. The data that has been collected were analyzed using descriptive and inferential statistical techniques. The results of data analysis showed that the average value of students' problem-solving ability results in the experimental class was 91.57 higher than the control class 83.67, however the variety of data in the control class tended to be 4.45 better than the experimental class 7.61. The problem-solving ability of class taught using Problem Based Learning with the problem-solving ability of class taught using conventional learning showed that there was no significant difference. This can be seen from the results of the analysis using the Mann Whitney test with a significance level of 5%, it appears that the value of p (sig.(2-tailed)) = 0.782 < = 0.05; This means that H0 is accepted